2021
DOI: 10.1111/os.13144
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Cerclage Wiring Combined with Cephalomedullary Nailing for Irreducible Subtrochanteric Fractures

Abstract: Objective To explore the surgical method, operation essentials and the clinical effect of the treatment of irreducible subtrochanteric femoral fractures by percutaneous cerclage wiring and Cephalomedullary nail. Method From February 2016 to October 2019, 17 cases of irreducible subtrochanteric femoral fractures (SFFs) treated via a minimally invasive wire system and intramedullary nail fixation were reviewed retrospectively. Ten male and seven female patients were involved. The average age was 59.88 ± 16.13 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…21 Cerclage cable is the most common medial support reconstruction technique in cephalomedullary nailing for trochanteric fractures, 22 but whether cerclage can improve fixation is still controversial. 23,24 Ceynowa et al confirmed that medial wall reconstruction with a cerclage cable does not improve axial stability of the fixation through biomechanical study. 25 Cement augmentation for trochanteric fractures is considered viable to limit the excessive sliding by enhancing the implant anchorage within the head and neck fragment and lead to promote patient early mobilization.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…21 Cerclage cable is the most common medial support reconstruction technique in cephalomedullary nailing for trochanteric fractures, 22 but whether cerclage can improve fixation is still controversial. 23,24 Ceynowa et al confirmed that medial wall reconstruction with a cerclage cable does not improve axial stability of the fixation through biomechanical study. 25 Cement augmentation for trochanteric fractures is considered viable to limit the excessive sliding by enhancing the implant anchorage within the head and neck fragment and lead to promote patient early mobilization.…”
Section: Introductionmentioning
confidence: 99%
“…Some techniques are available to enhance cephalomedullary nailing for unstable trochanteric fractures to reduce the risk of implant failure by restoring mechanical conduction of the medial femur and limiting excessive sliding 21 . Cerclage cable is the most common medial support reconstruction technique in cephalomedullary nailing for trochanteric fractures, 22 but whether cerclage can improve fixation is still controversial 23,24 . Ceynowa et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation